Analysis of the effectiveness rate of rapid serological tests for COVID-19 registered in ANVISA, a systematic review in the literature (Research, Society and Development, 2021)
Introduction: The immunological tests for COVID-19 have the great advantage of their diagnostic speed, but their efficiency rate varies depending on the manufacturer, generating the need to identify the best tests to be used in order to avoid false diagnoses. Objective: To point out the tests available in Brazil, which within the clinical trials sought, have a better rate of effectiveness. Methods: Articles referring to clinical trials that test the effectiveness of rapid tests for the detection of anti-SARS-COV-2 immunoglobulins were searched in the literature. For this purpose, a systematic search was carried out in the SCIELO, LILACS, PUBMED and MEDLINE databases using the descriptors SARS-COV-2, ELISA, COVID-19 and Assessment in association using the Boolean operator AND, followed by the application of criteria for inclusion and exclusion to select the papers to be included in the review. Results: 16 articles that tested 18 of the rapid tests available in the country were included. Conclusion: serological tests are a valuable tool to fight the SARS-COV-2 pandemic, but should not be used as a single tool in the diagnosis of viral infection given the period of immunological window. The ideal use of the tests will occur in cases where the patient already has more than 14 days of symptoms. The One Step COVID-2019 test from Guangzhou Wondfo Biotech revealed the best performance among those analyzed.